The Development of Science Laboratory Safety Educational Comic for Secondary School Students in Malaysia - Shaafi, Nur Farha; Yusof, Mohammad Mubarrak Mohd; Nasir, Suraya Md.; Ellianawati, Ellianawati (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2025)
The traditional method of teaching science laboratory safety often involves lengthy, complex manuals that are difficult for students to understand. Despite the existence of the School Science Laboratory Management and Safety (SLMS) guidebook, students’ knowledge and awareness of lab safety remain low. Research shows that comics can enhance students’ interest and understanding of safety protocols. This study aimed to develop a science laboratory safety educational comic for secondary school students to raise awareness about lab safety. The educational comic was developed following the analysis, design, development, implement, and evaluate (ADDIE) model, with this study focusing on the first three stages. A needs analysis involved questionnaires given to 131 students in Kuala Lumpur and Kedah, revealing a moderate awareness of lab regulations (average score: 3.53) and strong support for developing a safety educational comic (average score: 3.90). The educational comic, designed by six experts from university academic and science teachers, and illustrated by a professional illustrator, covers topics such as laboratory preparation, waste disposal, laboratory accidents, and fire extinguishers. Validation was performed by experts in materials aspect (2 education academic experts), learning aspect (2 science teachers), and media design aspect (2 art and design academic expert), with scores of 4.80, 4.85, and 4.65, respectively, indicating high qualifications. In conclusion, the science laboratory safety educational comic was found to be valid and highly effective in meeting educational standards for lab safety.